From Students, For Students: Applying Constructivist Theory in Learning and Enhancing Religious Moderation Awareness Among Students - Hidayat, Samsul; Wahab; Kurniawan, Syamsul; Sari, Nopita (Universitas Islam Negeri Raden Intan Lampung, 2025)
This paper aims to examine the application of constructivist theory in the learning process within the Islamic Religious Education Study Program at IAIN Pontianak and its impact on students' awareness of religious moderation. The research employs a library-based approach enriched by field investigations, including observation, interviews, and documentation. A descriptive method is used to analyze the implementation of constructivist theory in Islamic Religious education and its influence on students’ moderate attitudes. The findings indicate that constructivist-based learning not only enhances students’ theoretical understanding of religion but also fosters the development of moderate, inclusive, and tolerant attitudes toward diversity. By internalizing the values of moderate Islam, students are better equipped to resist extremist interpretations. The study concludes that the application of constructivist theory in the Islamic Religious Education Study Program at IAIN Pontianak plays a significant role in cultivating students’ awareness of religious moderation, thereby preparing them to become educators who promote peace, tolerance, and social harmony.